2020
DOI: 10.3389/fped.2020.00150
|View full text |Cite
|
Sign up to set email alerts
|

Voice and Exercise Related Respiratory Symptoms in Extremely Preterm Born Children After Neonatal Patent Ductus Arteriosus

Abstract: Objective: To investigate voice characteristics and exercise related respiratory symptoms in extremely preterm born 11-year-old children, focusing particularly on associations with management of a patent ductus arteriosus (PDA). Study design: Prospective follow-up of all children born in Norway during 1999-2000 at gestational age <28 weeks or with birthweight <1,000 g. Neonatal data were obtained prospectively on custom-made registration forms completed by neonatologists. Voice characteristics and exercise rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…5,6,37 More than half of all children (52%) in our study had been diagnosed with speech disorders, including impaired articulation and language development, and 13% had vocal cord paresis, which may impact both their voice and their respiration. 38 It is challenging to achieve optimal growth in those born EPT during the neonatal period and childhood. One study reported that children who were born EPT demonstrated catch-up growth in weight and length during childhood, but not head circumference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,37 More than half of all children (52%) in our study had been diagnosed with speech disorders, including impaired articulation and language development, and 13% had vocal cord paresis, which may impact both their voice and their respiration. 38 It is challenging to achieve optimal growth in those born EPT during the neonatal period and childhood. One study reported that children who were born EPT demonstrated catch-up growth in weight and length during childhood, but not head circumference.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of all children (52%) in our study had been diagnosed with speech disorders, including impaired articulation and language development, and 13% had vocal cord paresis, which may impact both their voice and their respiration. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The flow diagram of the search process is shown in Figure S1 . Of 2130 potentially relevant studies, 146 (including 357,781 infants) were included [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ,…”
Section: Resultsmentioning
confidence: 99%
“…In preterm infants, the closure is often delayed due to a lower intrinsic tone of the ductus and increased ductus sensitivity to the vasodilating effects of prostaglandin E2 and nitric oxide (NO) [ 1 ]. There is an inverse relationship between the rate of ductal closure and the birth weight (BW) and gestational age (GA) [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%